Electrostatic ignitions of fires and explosions - Pratt, Thomas H. (American Institute of Chemical Engineers, 2000)
Tom Pratt, a long-time process safety practitioner and lecturer in electrostatic safety, wrote this book to educate industry in the basics of electrostatics. It offers a selected collection of information designed to give readers the tools they need to examine the hazard potential of common industrial processes. Among the topics addressed are separation and accumulation of charge, discharge, minimum ignition energies, discharge energies, electrification in industrial processes, design and operating criteria, measurements, quantification of electrostatic scenarios. A selection of case histories.
Keywords: Static electricity and fires.; Explosions.; Electric spark.; Fire investigation.; elektronické knihy; electronic books